2015
DOI: 10.1016/j.febslet.2015.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary analysis of the global landscape of protein domain types and domain architectures associated with family 14 carbohydrate‐binding modules

Abstract: a b s t r a c tDomain promiscuity is a powerful evolutionary force that promotes functional innovation in proteins, thus increasing proteome and organismal complexity. Carbohydrate-binding modules, in particular, are known to partake in complex modular architectures that play crucial roles in numerous biochemical and molecular processes. However, the extent, functional, and evolutionary significance of promiscuity is shrouded in mystery for most CBM families. Here, we analyzed the global promiscuity of family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Disulfide bond assignment has shown that Cf-Avr4 contains a disulfide-bond pattern similar to carbohydrate-binding module family 14 (CBM14) lectins, suggesting that Cf-Avr4 utilizes a CBM14 fold to interact with chitin (van den Burg et al, 2003). CBM14s are modules of roughly 65 to 70 residues that bind specifically to chitin, a b(1-4) linked N-acetyl-D-glucosamine (GlcNAc) polysaccharide, which is a major structural constituent of the fungal cell wall and a potent inducer of PTI in plants (Suetake et al, 2000;Boraston et al, 2004;Chang and Stergiopoulos, 2015a). To date, a molecular-based mechanistic understanding of the CBM14-ligand interaction is lacking and tertiary information on CBM14 lectins is restricted to tachycitin, a small antimicrobial chitin-binding lectin that is found in horseshoe crab hemocytes and exhibits local sequence similarity and a similar disulfide-bond pattern as predicted for Cf-Avr4 (Kawabata et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide bond assignment has shown that Cf-Avr4 contains a disulfide-bond pattern similar to carbohydrate-binding module family 14 (CBM14) lectins, suggesting that Cf-Avr4 utilizes a CBM14 fold to interact with chitin (van den Burg et al, 2003). CBM14s are modules of roughly 65 to 70 residues that bind specifically to chitin, a b(1-4) linked N-acetyl-D-glucosamine (GlcNAc) polysaccharide, which is a major structural constituent of the fungal cell wall and a potent inducer of PTI in plants (Suetake et al, 2000;Boraston et al, 2004;Chang and Stergiopoulos, 2015a). To date, a molecular-based mechanistic understanding of the CBM14-ligand interaction is lacking and tertiary information on CBM14 lectins is restricted to tachycitin, a small antimicrobial chitin-binding lectin that is found in horseshoe crab hemocytes and exhibits local sequence similarity and a similar disulfide-bond pattern as predicted for Cf-Avr4 (Kawabata et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This search identified insect members of a Chitin Binding Protein (CBP) family, which comprises chitinases and peritrophic matrix proteins (Shen & Jacobs-Lorena, 1999). The CBP domain of these proteins belongs to the CBM14 family of carbohydrate-binding domains, also known as peritrophin-A domain in insects (Chang & Stergiopoulos, 2015). However, two major pieces of evidence indicate that Mmt/NPB are part of a distinct family of proteins: first, CBP proteins are characterized by a 6-cysteine motif instead of the 4-cysteine motif found in Mmt/NPB, and a few highly conserved aromatic residues (notably at position -3 before cysteine 3, and position 6 after cysteine 4), none of which are present in Mmt/NPB precursors.…”
Section: Resultsmentioning
confidence: 99%
“…Chitin is one of the most abundant structural polysaccharides in nature (Bai et al, 2016;Talamantes et al, 2016), and chitin degradation by chitinases is a critical process in the biogeochemical cycling of carbon and nitrogen in terrestrial and aquatic ecosystems (Bai et al, 2016). Biogenic sources of environmental chitin include fungi (Funkhouser and Aronson, 2007), arthropods (Merzendorfer and Zimoch, 2003), marine invertebrates (Yoshioka et al, 2017), bacteria (Chang and Stergiopoulos, 2015), and corals (Bo et al, 2012). However, chitin is produced mainly by arthropods and fungi, and is thought to be present in higher abundance today in the terrestrial, rather than marine, system (Talamantes et al, 2016) following the terrestrialization of arthropods, sometime after the Cambrian (Schwentner et al, 2017).…”
Section: Environmental Distribution Of Chitinmentioning
confidence: 99%
“…There are two main families of chitinases: glycoside hydrolase family 18 (GH18) and glycoside hydrolase 19 (GH19) (Funkhouser and Aronson, 2007). GH18 chitinases are distributed across the three domains of life (Chang and Stergiopoulos, 2015;Funkhouser and Aronson, 2007), whereas GH19 chitinases are restricted mostly to plants and are rarely associated with bacteria (Chang and Stergiopoulos, 2015). In one well-studied bacterial model organism, Streptomyces, there were ten genes associated with the GH18 family of chtinases (homologs chiA-E, and H-L) and two genes associated with GH19 (chiF, G) (Ubhayasekera and Karlsson, 2012).…”
Section: The Evolution Of Chitinase Gene Familiesmentioning
confidence: 99%